Education, judiciary and Constitution, 1978-2020 (II). The mental and educational rights of minors - Viñao Frago, Antonio (Historia y Memoria de la Educación, 2021)
This essay concerns the respect in Spain of the mental, (in)formative, and educational rights recognized in the 1989 Convention on the Rights of the Child, especially in relation to the rights of parents to have their children receive religious and moral training in accordance with their convictions (art. 27.3 of 1978 Constitution). After a historical reference to the aforementioned rights of minors, the article offers an analysis of the Convention and its legal development in Spain; the nature, propietorship and limits of the rights alluded to of the parents; the child’s freedom of thought, conscience and religion; and the judicial treatment of both rights in cases of divergence or conflict are analysed.